Endoscopic Management of Lacrimal System Dysgenesis and Dacryocystoceles in Fraser Syndrome: A Case Report and Literature Review - Megan E. Falls BA (Allergy & Rhinology, 2018)
Background Fraser syndrome is an autosomal recessive disorder characterized primarily by syndactyly, cryptophthalmos, urinary tract anomalies, ambiguous genitalia, and laryngeal anomalies. A 28-year-old man with Fraser syndrome presented with cryptophthalmos, microphthalmia, lacrimal system dysgenesis, and chronic sinusitis. Objective The patients’ clinical condition and surgical treatment are described. A literature review was conducted, and articles relevant to the case are presented. Methods Case report. Results To our knowledge, this is the first published case report of endonasal management of dacryocystoceles in a Fraser syndrome patient. The patient was treated via endoscopic endonasal marsupialization and drainage. Conclusion Fraser syndrome patients may initially present to many different specialties as the spectrum of clinical manifestations is broad. Physicians treating these patients should take a collaborative approach to surgical and medical management.